The Effect of Organizational Culture, Personality, Teamwork, Procedural Justice, and Organizational Citizenship Behavior on Job Tomori Pertamina North Sulawesi - Ida Farida; Syarifudin Tippe; Billy Tunas (Fakultas Ekonomi, Universitas Negeri Jakarta, 2019)
Organizational Citizenship Behavior was a part of the development concept in human resources management. This concept can support an organization’s progress in a positive direction. So the role of OCB becomes very important for the development of the organization. The research was aimed at finding out the information about the effect of organizational culture, personality, teamwork, procedural justice, and organizational citizenship behavior on Job Tomori Pertamina North Sulawesi. A survey was used by involving 250 employees as a sample. There were five instruments for measuring, organizational culture (31 items, rel .705, personality (25 items rel .969), teamwork (36 items rel .635), procedural justice (20 items rel .660), and organizational citizenship behavior (27 items rel .959). Data were analyzed by descriptive statistical analysis, inferential statistics for linearity test and path analysis. Organizational citizenship behavior significantly affected directly by organizational culture. Moreover, procedural justice directly significantly affected organizational citizenship behavior. Based on those findings, it can be concluded that it was personality and teamwork only which should be considered if organizational citizenship behavior would be improved. It can be stated that considering those findings, personality and teamwork could not be neglected in enhancing organizational citizenship behavior.